1995
DOI: 10.1073/pnas.92.15.6788
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin 1 expression in transformed endothelial cells restores a normal phenotype and suppresses their tumorigenesis.

Abstract: Murine endothelial cells are readily transformed in a single step by the polyomavirus oncogene encoding middle-sized tumor antigen. These cells (bEND.3) form tumors (hemangiomas) in mice which are lethal in newborn animals. The bEND.3 cells rapidly proliferate in culture and express little or no thrombospondin 1 (TS1). To The thrombospondins are a multigene family of modular glycoproteins involved in regulation of adhesion, migration, and proliferation of a number of normal and transformed cell types (1-4). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
138
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(158 citation statements)
references
References 30 publications
19
138
1
Order By: Relevance
“…Several functions have been attributed to TSP-1 including antiangiogenic [14,38] and proatherogenic [36,40] properties. More recently, this protein has been studied as a potential link between vasculature mechanisms and hyperglycemia [2,39].…”
Section: Discussionmentioning
confidence: 99%
“…Several functions have been attributed to TSP-1 including antiangiogenic [14,38] and proatherogenic [36,40] properties. More recently, this protein has been studied as a potential link between vasculature mechanisms and hyperglycemia [2,39].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that its expression can be positively regulated by P53 (Dameron et al, 1994), RB (Salnikow et al, 1994), nm-23 and one or more unknown genes on chromosome 10q (Hsu et al, 1996). Several lines of evidence suggest that THBS1 is an inhibitor of angiogenesis: (i) THBS1 is present in quiescent vessels and decreased or absent in actively forming endothelial sprouts or cultured endothelial cells forming tubules (Can®eld and Schor, 1995;DiPietro et al, 1994); (ii) THBS1 expression is shut o in rapidly growing endothelial cells from mouse hemangiomas induced by the polyoma virus middle t antigen (Sheibani and Frazier, 1995); (iii) wild type P53 inhibits angiogenesis by stimulating the production of THBS1 in ®broblast cells (Dameron et al, 1994); (iv) THBS1 inhibits endothelial cell adhesion, growth and motility in response to angiogenic stimuli (Panetti et al, 1997), and it also has the ability to induce apoptosis in endothelial cells (Guo et al, 1997); and (v) downregulation of THBS1 expression in endothelial cells enhances in vitro angiogenesis (DiPietro et al, 1994). Thus, THBS1 appears to be a potent anti-angiogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have implicated alterations in THBS1 expression in the neovascularization observed in human cancers (Roberts, 1996): Decreased expression of THBS1 has been reported in multiple primary tumors (Grossfeld et al, 1997;Zabrenetzky et al, 1994;Clezardin et al, 1993) and cells transformed in vitro by c-jun (Mettouchi et al, 1994), Nickel (Salnikow et al, 1994), v-src (Slack and Bornstein, 1994), the polyoma virus middle-t antigen (Sheibani and Frazier, 1995), and v-myc (Tikhonenko et al, 1996). Reexpression of THBS1 reduced tumor growth, angiogenesis and metastasis in a hemangioma cell line (Sheibani and Frazier, 1995) and a breast cancer cell line (WeinstatSaslow et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many, but not all, transformed cell lines express very low levels of TSP1 (Mettouchi et al, 1994;Salnikow et al, 1994;Slack and Bornstein, 1994;Sheibani and Frazier, 1996;Tikhonenko et al, 1996). In some cases, re-expression of TSP1 in transformed cells suppresses their tumorigenicity (Weinstat et al, 1994;Sheibani and Frazier, 1995).…”
mentioning
confidence: 99%